2002
DOI: 10.1210/mend.16.1.0748
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Rapid Estrogen Action to MAPK Activation by ERα-Shc Association and Shc Pathway Activation

Abstract: E2 rapidly activates MAPK in breast cancer cells, and the mechanism for this effect has not been fully identified. Since growth factor-induced MAPK activation involves signaling via the adapter protein Shc (Src-homology and collagen homology) and its association with membrane receptors, we hypothesized that breast cancer cells utilize similar signaling mechanisms in response to E2. In the present study, we demonstrated that E2 rapidly induced Shc phosphorylation and Shc-Grb2 (growth factor receptor binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 63 publications
5
155
0
4
Order By: Relevance
“…ERa association with cytoplasmic signaling molecules is not unusual. Recently, ERa has been shown to bind the PI-3K/Akt complex (Simoncini et al, 2000;Sun et al, 2001), and to interact with growth factor receptor docking protein Shc (Song et al, 2002) as well as with IGF-IR (Kahlert et al, 2000). Similarly, we reported that unliganded ERa can associate with cytoplasmic IRS-1 in MDA-MB-231/ER cells (Morelli et al, 2003).…”
Section: Discussionmentioning
confidence: 58%
“…ERa association with cytoplasmic signaling molecules is not unusual. Recently, ERa has been shown to bind the PI-3K/Akt complex (Simoncini et al, 2000;Sun et al, 2001), and to interact with growth factor receptor docking protein Shc (Song et al, 2002) as well as with IGF-IR (Kahlert et al, 2000). Similarly, we reported that unliganded ERa can associate with cytoplasmic IRS-1 in MDA-MB-231/ER cells (Morelli et al, 2003).…”
Section: Discussionmentioning
confidence: 58%
“…In this report, we demonstrated that MAPK induced ERa activation (cross-talk) in MEK/MCF-7 cells leads to estrogenindependent ER phosphorylation and ERE-reporter transcriptional activity. ER transcriptional activity can also be enhanced by non-genomic E 2 -mediated signaling in some cell lines (Castoria et al, 1999;Song et al, 2002). When MCF-7/MEK and MCF-7 control cells were treated with membrane impermeable BSA conjugated E 2 , no ERE transcriptional activity was detected ruling out the possible non-genomic e ects of E 2 in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…ERs can interact with caveolin-1 and are localized to caveolae raft domains isolated from plasma membranes of endothelial cells (Schlegel et al, 1999;Razandi et al, 2002). Imaging analysis of endogenous ERa in MCF7 breast cancer cells shows a pool of receptors near the plasma membrane (Song et al, 2002). In the presence of E2, there is increased membrane ruffling and increased association of ERa on the extending filipodia.…”
Section: Rapid E2 Actions -Localization Of Relevant Er Formsmentioning
confidence: 99%
“…ERs have also been proposed to couple directly or functionally with G proteins Gaq and Gai, leading to downstream signaling through PKC, PLC, and c-Src (reviewed in Levin, 2003). ERa association with the adaptor molecule Shc occurs within 3 min of E2 treatment in MCF7 and long-term estrogen-deprived (LTED) MCF7 cells, resulting in Shc and MAPK phosphorylation (Song et al, 2002). The phosphorylation responses to E2 were inhibited by antiestrogens and by pharmacological inhibitors of c-Src.…”
Section: Intracellular Signaling Partners Of Ermentioning
confidence: 99%